Managmante And Determining the Employment Status of Sports Science Graduates of Islamic Azad Universities Using the CIPPO Model - RANGIAN, MOJGAN; PEYMANIZAD, DR. HOSSEIN; ESMAILZADEH, DR. MOHAMMAD REZA (The journal of contemporary issues in business and government, 2021)
The aim of the present study was to determine the employment status of sports science graduates of Islamic Azad universities using systems thinking. The method of the present research was mixed and of analytical exploratory type which is a part of developmental research according to this approach. First, a research questionnaire was designed using interviews with sports management professors, entrepreneurs and sports employers according to the data theory of the foundation and systems thinking. Then, the face and content validity was approved by experts in the field of sports management and distributed in the statistical community, in which a total of 352 questionnaires were correctly distributed and collected. One-sample t-test was used to determine the employment status of graduates and TOPSIS model was used to prioritize systemic thinking factors in graduate employment. The results showed that the status of "outcome" and "output" factors was not favorable, but the factors of "context", "input" and "process" were also favorable. Also, the results of TOPSIS model showed that "field" was in the first place, "process" was in the second place, "input" was in the third place, "input" was in the fourth place, "output" and finally "consequence" was in the fifth place from the point of view of priority. In a general conclusion, it should be stated that the trustees of the Islamic Azad University should try to create an entrepreneurial spirit among the students. Because in today's world, many businesses are created by entrepreneurship and innovation that did not exist before. In other words, instead of needs assessment, needs should be created.